Organizational ambidexterity model proposal - Garzón Castrillon, Manuel Alfonso (2020)
In this review article, the inherent aspects with the foundations of organizational ambidexterity are addressed, namely: the background of organizational ambidexterity, definitions of ambidexterity; Typologies of structural, sequential and contextual ambidexterity, from the strategic direction, an organizational ambidexterity model is proposed from which its variables are addressed: organization-prior knowledge and experience; ambidextrous search and performance of knowledge; individual ambidexterity; Organizational ambidexterity, innovation, and business results, six discussion hypotheses and conclusions are established.